Acceptability of a Social Learning Theory-based parenting programme to South African parents - Wilson, Katherine (Department of Psychology, 2026)
Good parenting practices significantly contribute to child development and wellbeing. Evidence shows that optimal child development occurs in environments where parents are nurturing, warm and supportive, while harsh parenting styles negatively impact children's mental health and developmental outcomes. This study explores the acceptability of the ParentChat programme among South African parents who participated in its pilot implementation. ParentChat, an adaptation of the Parenting for Lifelong Health programme, is a digital, group-based family-strengthening initiative aimed at improving parenting skills, delivered through WhatsApp. Programme acceptability was operationally defined as whether parents had used techniques taught, or were likely to use them. Conducted in four South African provinces, the study employed a sequential explanatory mixed methods design using quantitative surveys and in-depth qualitative interviews. 286 parents participated in the study; there were 337 quantitative surveys completed by parents over four weeks. Ten initial follow up qualitative interviews were completed by parents in the Western Cape one month after completion of the programme and twenty-seven follow up qualitative interviews were completed by the parents eighteen months after the programme. Template analysis was used to code, describe, organise and analyse the data thematically from the qualitative interviews from the participants' perspective. Findings revealed that despite initial scepticism about the programme's cultural relevance, parents widely adopted and valued the skills taught, such as spending one-on-one time with their children, talking about emotions, praising their children and giving clear and realistic instructions. Findings also showed acceptability for conducting the programme digitally on WhatsApp. Parents reported shifts from authoritarian to a more child-centred approach, reductions in verbal and physical violence, better communication and improvements in family dynamics and child behaviour. The study highlights the importance of adaptations in parenting interventions and underscores the potential of digital platforms to deliver accessible and effective family support in low-resource settings.